2011
DOI: 10.1186/1471-2156-12-80
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of genomic selection in simulated populations mimicking the extent of linkage disequilibrium in beef cattle

Abstract: BackgroundThe success of genomic selection depends mainly on the extent of linkage disequilibrium (LD) between markers and quantitative trait loci (QTL), the number of animals in the training set (TS) and the heritability (h2) of the trait. The extent of LD depends on the genetic structure of the population and the density of markers. The aim of this study was to calculate accuracy of direct genomic estimated breeding values (DGEBV) using best linear unbiased genomic prediction (GBLUP) for different marker den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 17 publications
(19 reference statements)
7
57
2
1
Order By: Relevance
“…Taken together, our current results (50K vs. 80K) and the results of other genomic evaluation studies (777K vs. 50K) suggest that there are no significant differences in prediction accuracies by simply increasing SNP density. These are contrary to the expectation that the accuracy of genomic prediction could improve as a result of an increased degree of linkage disequilibrium (ld) between SNP markers and QTL (Meuwissen and Goddard, 2010) and the result that the extent of LD had major impact on the prediction accuracy in simulation study (Brito et al, 2011). The reason why this expectation was not realized could be due to a general lack of strong LD between markers and QTL and the fact that adding additional noninformative SNP simply adds an additional source of noise to prediction equations.…”
Section: Discussioncontrasting
confidence: 50%
“…Taken together, our current results (50K vs. 80K) and the results of other genomic evaluation studies (777K vs. 50K) suggest that there are no significant differences in prediction accuracies by simply increasing SNP density. These are contrary to the expectation that the accuracy of genomic prediction could improve as a result of an increased degree of linkage disequilibrium (ld) between SNP markers and QTL (Meuwissen and Goddard, 2010) and the result that the extent of LD had major impact on the prediction accuracy in simulation study (Brito et al, 2011). The reason why this expectation was not realized could be due to a general lack of strong LD between markers and QTL and the fact that adding additional noninformative SNP simply adds an additional source of noise to prediction equations.…”
Section: Discussioncontrasting
confidence: 50%
“…The reliability of GEBV prediction depends on the level of linkage disequilibrium between markers and QTL in both within family or population-wise scenarios (Hayes et al 2009). Increasing the density of markers would increase the level of linkage disequilibrium between markers and QTL that, in turn, would increase the accuracy of GEBV (Brito et al 2011) till a maximum of accuracy that depend on the genetic architecture of the traits. The level of linkage disequilibrium is larger in livestock populations than in humans.…”
Section: Genomic Selection In Pig Populationsmentioning
confidence: 99%
“…With GS in beef cattle in its infancy, there is limited evidence in the literature with which to compare the genetic gains predicted in this study. Two other simulation studies, Brito et al (2011) and Van Eenennaam et al (2011), predicted increases in accuracy from the use of GS in terminal beef traits of similar magnitude to this study. Saatchi et al (2011) reported GBV accuracies of between 0.2 and 0.6 in an evaluation of 3570 US Angus bulls, which used deregressed EBV as phenotypes.…”
Section: Discussionmentioning
confidence: 68%
“…Given the need to estimate these parameters used in constructing this model, a weighted bending procedure was incorporated to make the correlation matrices positivedefinite (Jorjani et al, 2003). The pedigree-based estimate of Ne by Bouquet et al (2010) for the Irish Limousin population (a population of similar size and genetic origin to that in the United Kingdom), of~300, was adopted for the current study. The bovine autosomal chromosome lengths were taken from Deukwhan and Vasco (2011).…”
Section: Methodsmentioning
confidence: 99%